MicroRNAs in circulating extracellular vesicles as biomarkers of early colorectal cancer captured using high mannose N-glycan-specific lectin from Oscillatoria Agardhii - Nakayama, Sanae; Umeda, Miyabi; Kobayashi, Kenya; Nakano, Yukiko; Hori, Kanji; Umemura, Tsukuru; Kurokawa, Hiroshi (Frontiers in Oncology, 2025)
IntroductionLectin (OAA), isolated from the filamentous cyanobacterium Oscillatoria agardhii, exhibits high specificity and strong binding affinity for high-mannose (HM) N-glycans. Previous studies have demonstrated that OAA captured extracellular vesicles (EVs) derived from cancer cell lines. This study aimed to confirm the effectiveness of OAA in capturing HM N-glycans in blood and explore its potential in capturing circulating EVs derived from early-stage colorectal cancer (CRC) tumors.MethodsOAA1 (a recombinant OAA variant) was used to capture HM N-glycans from blood samples. The ability of OAA1 to capture circulating EVs in patients with stage I CRC was assessed. The miRNA profiles of the OAA1-captured EVs were analyzed and compared between 60 patients with stage I CRC and 60 healthy controls. Statistical analyses were performed to evaluate the potential of the specific miRNAs as CRC biomarkers.ResultsOAA1 effectively captured HM N-glycans in the plasma. Nanoparticle and immunoblot analyses confirmed the presence of EVs in the OAA1-captured from plasma. The miRNA profile of OAA1-captured EVs exhibited characteristics of patients with CRC. Statistical analysis identified five miRNAs (miR-122-5p, miR-130a-3p, miR-146a-5p, miR-15b-5p, and miR-126) and three internal control miRNAs (miR-93-5p, miR-192-5p, and miR-502-5p) with a high potential for cancer separation (area under the curve (AUC) = 0.948; sensitivity = 0.883; specificity = 0.933).DiscussionThese results suggest that circulating miRNAs in OAA1-captured EVs could serve as biomarkers for the surveillance of early stage CRC using liquid biopsy. The OAA1-immobilized column device facilitates easier and quicker inspection processes and accentuates differences in circulating miRNAs associated with the disease.ConclusionOAA1-column showed potential clinical application to analyze circulating EVs and miRNAs associated with CRC, serving as a relevant liquid biopsy for early cancer detection.